PRAGMATIC AND LINGUISTIC FEATURES OF BUSINESS CORRESPONDENCE TEXTS - Kholmatova Guzal Bakhodirovna (Bright Mind Publishing, 2025)
This paper investigates the pragmatic and linguistic features of business correspondence texts from a theoretical and functional perspective. It examines how pragmatic categories such as communicative intent, addressivity, modality, and politeness shape written interactions in professional communication. By analyzing contracts and business letters, the study demonstrates that pragmatic meaning in business discourse is not limited to literal semantics but reflects social hierarchy, institutional norms, and interpersonal strategies. The paper also highlights cross-cultural differences between Uzbek and English business communication, emphasizing the importance of pragmatic competence in international correspondence.
Keywords: Pragmatics, pragmalinguistics, business communication, speech act theory, politeness, addressivity, pragmatic effect.